Systematic revision reveals underestimated diversity of the South African endemic fishfly genus Taeniochauliodes Esben‐Petersen (Megaloptera: Corydalidae). (16th April 2013) - LIU, XINGYUE; PRICE, BENJAMIN; HAYASHI, FUMIO; DE MOOR, FERDINAND; YANG, DING
Abstract Taeniochauliodes is the most common and widely distributed fishfly genus in South Africa, with one historically recognized valid species Taeniochauliodes ochraceopennis Esben‐Petersen. The present systematic revision of Taeniochauliodes has found that this genus consists of at least eight species: T. angustussp.n., T. attenuatussp.n., T. barnardisp.n., T. fuscussp.n., T. minutussp.n., and T. natalensissp.n. Description of all new species and a redescription of T. esbenpetersenicomb.n. & stat.rev. and T. ochraceopennis are made. These species all have relatively narrowly confined distributions. An interspecific phylogeny of Taeniochauliodes is estimated based on adult morphological data. The historical biogeography of this genus is discussed based on the phylogenetic results and the present distribution of each species, suggesting that the origin of Taeniochauliodes likely dates back to the Late Cretaceous. The earliest branch, which separates T. natalensissp.n. from the remaining South African species, suggests an early vicariance event occurred between KwaZulu‐Natal and more western parts of South Africa. Furthermore, speciation within Taeniochauliodes is hypothesized to be correlated with fragmentation of its forest habitat during the Plio‐Pleistocene.